Entre mulheres, contemporaneidades e uma dose de violência: uma análise da obra Neighbours, de Lília Momplé - Franzini, Letícia Alves (Universidade Federal de São Carlos, 2025)
Based on the premise articulated by Francisco Noa in “Mozambican Literature and the Reinvention of Contemporaneity” (2015, p. 25-35), a text in which the author discusses the concept and how it manifests in the African literatures of Portuguese language, we seek to analyze the novel Neighbours (1995) by Mozambican writer Lília Momplé as a space for the elaboration of a multifaceted Mozambican contemporaneity (Noa, 2015), through its heterogeneity and conflicts, and to understand how it integrates “a literature that, open to the dynamics of the world, realizes within itself the multifaceted contemporaneities that ultimately compose the vital space in which it develops” (Noa, 2015, p. 34). We believe, therefore, that by reflecting on the relationship established between Mozambique and South Africa in the post-independence period, the conflicts that arise in this society, particularly during the Civil War, and through an analysis of the persistence of violent structures that serve as tools for the construction and maintenance of this society, Lília Momplé responds to the challenging task of recreating, through fictional vision, multiple compositions of the Mozambican being. Finally, we aim to understand and analyze the construction of these contemporaneities in Mozambique through Neighbours by Lília Momplé, as well as comprehend the insertion and representation of the feminine in this process.
Among women, contemporaneity and a dose of violence: an analysis of Neighbours, by Lília Momplé
Keywords: Contemporaneidade moçambicana; Violência; Representação feminina; Lília Momplé; LINGUISTICA, LETRAS E ARTES::LETRAS::OUTRAS LITERATURAS VERNACULAS